Magnetic resonance imaging of Hoffa's fat pad and relevance for osteoarthritis research: a narrative review. Issue 3 (March 2016) - Roemer, F.W.; Jarraya, M.; Felson, D.T.; Hayashi, D.; Crema, M.D.; Loeuille, D.; Guermazi, A.
Summary: Objective: To give an illustrative overview of Hoffa's fat pad pathology with a radiologic emphasis on the anatomy, on technical considerations, and on imaging differential diagnoses in the context of osteoarthritis (OA) imaging research. Design: A PubMed database search including only English literature and covering a 20 year period was performed. The search was based on but no limited to the query terms "Hoffa", "Hoffa's fat pad" or "infrapatellar fat pad (IPFP)" in combination with "synovitis", "OA", and "magnetic resonance imaging (MRI)". The literature search yielded 289 publications that were screened for relevance; additional references were included when these were considered of importance. Results: Several anatomic variants and pathologic conditions may be encountered when assessing Hoffa's fat pad including tumors and tumor-like lesions such as osteochondroma, tenosynovial giant cell tumor (TGCT) (and pigmented nodular synovitis) and arthrofibrosis, traumatic changes including contusions and anatomic variants such as recesses. The latter may be accountable for differences in cross-sectional area or volume changes over time. Signal changes are commonly used in OA research as surrogate markers for synovitis but are non-specific findings. Conclusions: Quantitative approaches to evaluate 3D parameters of Hoffa's fat pad are increasingly applied and their role in regard to structural progression and clinical manifestations of disease needs to be further elucidated. In applying such approaches, knowledge of the detailed anatomy and potential pitfalls that may be a result of anatomical variants, inflammatory disease manifestations and additional diverse pathologies encountered seems to be paramount.